Evaluating Remedial Secession as a Legitimate Territorial Acquisition: Lessons from Eastern Ukraine 2022 - Miano, Muhammad Ryan Ramadhani; Handayani, Irawati; Cristianti, Diajeng Wulan (UIN Sunan Kalijaga Yogyakarta, 2024)
This study examines whether corrective secession can be considered a legitimate means of acquiring territory under contemporary international law, focusing on the secession referendum in Eastern Ukraine in 2022. Although the right to self-determination has evolved from a colonial context to broader applications, the legality of corrective secession in non-colonial situations remains controversial and under-explored. Previous research has largely focused on post-colonial cases such as Bangladesh and South Sudan, leaving a gap in understanding externally influenced secession movements. This article aims to address this gap through normative legal analysis, drawing on international legal instruments, state practice, and jurisprudence from the International Court of Justice and national courts. The findings of the study indicate that secession as a corrective measure can only be justified in exceptional cases where an ethnic group experiences ongoing and systematic discrimination, and where the parent state fails to provide an effective solution. When applied to Eastern Ukraine, this study finds no evidence of systematic human rights violations by the Ukrainian government that would justify secession. Instead, the conflict and referendum were largely triggered by external intervention, rendering such claims contrary to international law. This analysis reaffirms that the doctrine of secession as a remedy remains limited and exceptional, reinforcing the priority of territorial integrity in accordance with the UN Charter. This study contributes to the ongoing debate by clarifying the legal and moral thresholds for secession as a remedy, and provides a nuanced legal framework for assessing future claims of secession.